Audit of European Funds Destined to the Development of Agricultural Sector - Vârteiu Daniel Petru (Ovidius University Annals: Economic Sciences Series, 2018)
Romania has benefited until now by European funds destined to the development of agriculturalsector and rural environment during two periods of time: pre-adherence period 2000-2006 whenfunds were accessed through SAPARD program and the post- adherence period which isconstituted in two programming periods, namely programming period 2007-2013 andprogramming period 2014-2020 which allows accessing resources from the European AgriculturalGuarantee Fund (EAGF) and European Agricultural Fund for Rural Development (EAFRD). Theaudit of these certain European funds consists in an activity which is complexly developed both innational institutions such as Audit Authority, as well as in European institutions like EuropeanCourt of Auditors. Through the audit mission the acquiring of a reasonable insurance that theEuropean funds are managed and used in a correct manner, is aimed.